2019
DOI: 10.1002/psp.2249
|View full text |Cite
|
Sign up to set email alerts
|

Who can ride along? Discrimination in a German carpooling market

Abstract: Although numerous studies have focused on ethnic discrimination in the labour and housing market, carpooling has barely been covered. Yet carpooling is indispensable for many minorities because they face severe economic inequalities. In order to test for ethnic discrimination in the carpooling market, we conducted a correspondence test. We sent out requests from four fictitious user profiles to drivers listed on one of Germany's carpooling websites. All users were aged mid‐20s: two males and two females. One m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…Turkish minorities in Germany and Austria are more likely to experience statistical as well as taste-based ethnic discrimination in the labor market (e.g., Kaas and Manger 2012; Sachverst€ andigenrat deutscher Stiftungen fu ¨r Integration und Migration 2014; Weichselbaumer 2016Weichselbaumer , 2017, the rental market (e.g., Auspurg et al 2017;Lu ¨tkenho ¨ner 2014;Sawert 2019), in welfare offices (Hemker and Rink 2017), online auctions (Przepiorka 2011), schools (Sprietsma 2013), carpooling (Carol et al 2019), and the dating market (e.g., Lu ¨tkenho ¨ner 2014). Two studies discovered discrimination against Turkish minorities in interaction with gender on the market for student housing (Diehl et al 2013) and in dealing with public-sector bodies when requesting information on child care and mobile homes (Grohs et al 2016).…”
Section: T H E O R E T I C a L B A C K G R O U N Dmentioning
confidence: 99%
“…Turkish minorities in Germany and Austria are more likely to experience statistical as well as taste-based ethnic discrimination in the labor market (e.g., Kaas and Manger 2012; Sachverst€ andigenrat deutscher Stiftungen fu ¨r Integration und Migration 2014; Weichselbaumer 2016Weichselbaumer , 2017, the rental market (e.g., Auspurg et al 2017;Lu ¨tkenho ¨ner 2014;Sawert 2019), in welfare offices (Hemker and Rink 2017), online auctions (Przepiorka 2011), schools (Sprietsma 2013), carpooling (Carol et al 2019), and the dating market (e.g., Lu ¨tkenho ¨ner 2014). Two studies discovered discrimination against Turkish minorities in interaction with gender on the market for student housing (Diehl et al 2013) and in dealing with public-sector bodies when requesting information on child care and mobile homes (Grohs et al 2016).…”
Section: T H E O R E T I C a L B A C K G R O U N Dmentioning
confidence: 99%
“…Finally, Carol et al (2019) published a study in which providers of carpooling offers were contacted by supposedly German or Turkish users. The researchers collected 952 cases which clearly revealed that women with German names were least likely to experience discrimination, while men with Turkish names are the most likely to be discriminated against.…”
mentioning
confidence: 99%
“…These profiles foster a sense of personal contact (Dubois, Willinger, & Blayac, 2012;Guttentag, 2015) and to provide information that platform users use to assess the trustworthiness of their potential trading partners. However, an unintended consequence of these profiles is that they may lead to discrimination (Ahuja & Lyons, 2019;Carol, Eich, Keller, Steiner, & Storz, 2019;Cui et al, 2020;Edelman et al, 2017;Ert et al, 2016;Laouénan et al, 2017;. Names and photos convey information about users' demographic characteristics, of which ethnicity and nationality, gender, and age are the most obvious.…”
Section: Literature Review: Trust and Discrimination In Online Marketsmentioning
confidence: 99%